Wait, I'm the boss?!? : the essential guide for new managers to succeed from day one - Economy, Peter (Career Press, 2020)
"This book is chock-full of useful information, tips, and checklists that can be used by anyone who aspires to become a skilled manager. While it's written with the new manager in mind, it can also serve as a useful refresher for any manager, no matter how experienced he or she may be. This guide explores the fundamental skills that every manager needs to understand, practice, and master, such as, building teams and teamwork, setting goals, creating a fun and effective organizational culture, rewarding and motivating employees, leading organizational change, learning how to hire great employees, correcting poor performance, coaching and mentoring, delegation, communicating effectively, and dealing with layoffs and terminations"--